Meningkatkan Aktivitas Hasil Belajar PPKn Menggunakan PBL Kombinasi Poster Comment Talking Stick Kelas IVA SD - Mislian Dinda Norjanah; Khairil Anwar (Politeknik Kampar, 2023)
The problems that occur are students are not active in learning, students are not used to expressing opinions, and quickly get bored with the material being taught because learning is less varied. This study aims to describe the activities of teachers, students, and learning outcomes. The type of research applied is PTK with a qualitative and quantitative approach carried out for 4 meetings. The subject of the study was class IVA at SDN Jiwa Dalam 4 with 25 children. The results of the study showed that teacher activity at meeting I scored 36 good criteria, reached a score of 45 very good criteria at meeting IV. Student activities at meeting I got 56% activity with the criteria of being quite active and reaching 96% at meeting IV the criteria were very active. The learning outcomes of the first meeting were classically complete 40% and increased to 96% in the fourth meeting. The results of this study can be used as a reference in implementing the learning model. This research can be used as a reference in using learning models that can improve the quality of teacher activities, student activities and student learning outcomes.